Antena impressa de faixa ultra-larga empregando a geometria fractal do tapete de Sierpinski - Carleti, Monique (2015)
This paper presents the development of rectangular shaped printed antennas using the fractal geometry of the Sierpinski carpet. We show that the introduction of this geometry affects the resonance frequencies, bandwidth, reflection coefficient and gain, among other performance parameters of the antenna. Some models using FR4 substrate were designed and analyzed. Changes in the feeding system and in the geometry were carried out in order to expand the antenna?s usable frequency range. The final model was designed employing polytetrafluoroethylene substrate (PTFE) and coplanar waveguide (CPW) feeding system with some adaptations, aiming better frequency response. The prototype was tested to verify its behavior based on the analysis of the reflection coefficient, gain and radiation pattern. An ultra-wide band with multiple resonance points operation was found possible for the antenna.